Combined femtosecond intrastromal lenticular implantation and corneal crosslinking to treat advanced keratoconus: a 6-month observation including epithelial remodeling - Yahui Dong; Jing Zhang; Yafei Xu; Lihong Xu; Fangfang Sun; Jie Hou; Zhixing Ma; Yulin Lei (BMC Ophthalmology)
Abstract Purpose To evaluate the effect of combined femtosecond intrastromal lenticular implantation (FILI) and corneal crosslinking (CXL) in advanced keratoconus by reporting visual quality, biomechanics, curvature, and corneal epithelial remodeling. Methods Nine eyes from eight patients with advanced keratoconus were included in this retrospective study. All involved eyes underwent combined FILI and CXL. A femtosecond laser was used to create an intrastromal pocket with a 4 mm incision in the recipient cornea. A convex stromal lenticule, obtained by small incision lenticule extraction (SMILE) for myopia treatment, was then gently inserted into the intrastromal pocket through the 4 mm incision and flattened. Following this, the CXL procedure was performed on the operative eye. Follow-up evaluations were conducted before surgery and at 1,3, and 6 months postoperatively. Results We collected data before surgery and at 1, 3, and 6 months postoperatively for all involved keratoconus patients. Corneal biomechanical properties in all eyes improved significantly; SP-A1 increased from the preoperative value (36.17 ± 4.70) to 6 months postoperatively (53.47 ± 3.55, P = 0.008). ARTh increased from the preoperative value (129.19 ± 8.63) to 6 months postoperatively (320.61 ± 54.47, P = 0.015). The integrated radius decreased from the preoperative value (17.18 ± 3.26) to 6 months postoperatively (13.36 ± 2.64, P = 0.015). There was no statistical difference in DAR-2 mm and A1 velocity between preoperative and 1, 3, and 6 months postoperative time points (P = 0.651, P = 0.397). The central corneal thickness of all patients increased significantly and remained stable after surgery. The uncorrected distance visual acuity (UDVA) did not change significantly, but some patients wore rigid gas permeable contact lenses (RGPs) over 6 months after surgery and achieved a best-corrected visual acuity (BCVA) of LogMAR 0.2 to 0.0. The absolute value of spherical aberration in the 6th month decreased than that before the surgery (P = 0.028), and there was no significant change in higher-order aberrations and coma aberrations before and after the surgery. Following the surgery, the epithelium became thicker in both central 0-1 mm and peripheral 3.5–4.5 mm zones of the cornea, but showed no significant disparities within the paracentral 1–2.5 mm and 2.5–3.5 mm regions. The corneal epithelial thickness (CET) became more uniform overall. Conclusions Combined FILI and CXL appear to effectively thickened the cornea and improved the corneal biomechanics of advanced keratoconus, and prevented further development of keratoconus. The corneal epithelium thickened in both central and peripheral regions, and the distribution of corneal epithelial thickness became more uniform after surgery. We suggest that this change in the corneal epithelium may be related to a moderate rate of corneal thickness change after surgery (i.e. an increase in ARTh), rather than a change in the curvature of the anterior surface of the cornea.